2018
DOI: 10.1007/s00784-018-2371-8
|View full text |Cite
|
Sign up to set email alerts
|

Transmission patterns of Streptococcus mutans demonstrated by a combined rep-PCR and MLST approach

Abstract: Using a combined rep-PCR and MLST approach, it is possible to track probable transmission and strain sources for S. mutans genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that vertical transmission of S. mutans from mother to child and horizontal transmission from child to child are the two sources of S. mutans colonization in children [32,33]. MLST was used to evaluate the transmission of S. mutans [34,35]. In this study, we found that some children from the same kindergarten and from different kindergartens shared the single ST, indicating child-to-child transmission of S. mutans in Bengbu, China.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have shown that vertical transmission of S. mutans from mother to child and horizontal transmission from child to child are the two sources of S. mutans colonization in children [32,33]. MLST was used to evaluate the transmission of S. mutans [34,35]. In this study, we found that some children from the same kindergarten and from different kindergartens shared the single ST, indicating child-to-child transmission of S. mutans in Bengbu, China.…”
Section: Discussionmentioning
confidence: 61%
“…However, this analysis had not been used to genotype S. mutans strains. For the genotyping of S. mutans, the techniques of AP-PCR (11), rep-PCR, and MLST (13) have been used so far. However, these techniques are usually more laborious and expensive, so the use of the 16S rRNA gene PCR-RFLP analysis offers a simpler and cheaper method to compare genotypic diversity and stability of S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods have been used to identify the mutans streptococci (MS) diversity, such as DNA genomic fingerprinting by pulse-field gel electrophoresis (PFGE) (12), arbitrary-primer polymerase chain reaction (AP-PCR) (11), repetitive extragenic palindromic PCR (rep-PCR), and multilocus sequence typing (MLST) (13). PCR based upon the dexA gene sequence has been successfully applied for the identification of S. mutans species.…”
Section: Introductionmentioning
confidence: 99%
“…Reported patterns of S. mutans transmission include mother-to-child transmission, father-to-child transmission, intrafamilial transmission, and child-to-child transmission (39)(40)(41). In previous studies of S. mutans, evidence of transmission among children and their family members was defined via MLST based on identical ST assignments (17,40).…”
Section: Fig 4 Legend (Continued)mentioning
confidence: 99%